Didactic Conditions of Implementing the Process of Preparing Future Vocational Education Teachers for Computer Modeling - Dadaboyeva Zulhumor Matkarim qizi (Researchparks Publishing, 2022)
In this article, the didactic conditions for the implementation of the process of preparing future vocational teachers for computer modeling were studied.